(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The first book of Amish Tripathi. The Meluha immortals (Shiva Trio I) can be read in a number of metaphysical forms. Amish Tripathi has demonstrated an incomparable brilliance in the recreation of Hindu mythology. A recent Indian British writer His Shiva, a Tibetan refugee, migrates to Meluha to lead revenge and kill evil from Suryavanshi. The clan of Shiva is another diasporic community. Shiva cannot be described as leader of the group from a conventional diasporic point of view. Shiva’s diasporic culture is not shared with traditional diasporic experience of migration, displacement, isolation, longing, a search for home countries and identity crisis. In reality, the Meluhan scheme of things satisfies the tribe the majesty of Meluhan has intrigued its mind. Amish humanized mythological characters and figures. His Sati is a woman of Vikrama, who is meant to bear poor destiny she has a very unusual awareness of the fighting arts, while she is a subaltern. Fiction feminist should not claim constitutional freedom, economic privileges and societal identity she is an incarnation of greatness and creativity. Lady Ayurvati is an accomplished, qualified doctor who has both medical prescription and surgical abilities. Kanakhala is Emperor Daksha’s Prime Minister and is responsible for financial affairs, revenue and protocol. The document may be ecocritical spoken of as well.